Prediksi Perubahan Tutupan Lahan di Kecamatan Sirimau, Kota Ambon Menggunakan Celular Automata- Markov Chain - Nadhi Sugandhi; Supriatna Supriatna; Eko Kusratmoko; Heinrich Rakuasa (JPG (Jurnal Pendidikan Geografi), 2022)
Sirimau District has the largest population in Ambon City which has an impact on the need for higher residential land, this will certainly affect uncontrolled land cover changes and have an impact on land conversion and environmental damage. This study aims to analyze land cover changes in Sirimau District in 2012, 2017, and 2022, and predict land cover in 2031. This study uses the Cellular Automata Markov Chains (CA-MC) method. The results showed that in the period 2012-2031 the area of residential land cover and open land continued to increase along with the increase in population and the high need for built-up land. In contrast to the land cover of agricultural areas and non-agricultural areas, which experienced a decrease in area. The results of the research are expected to be used as a basis for making policies related to the arrangement and good use of space in the future